The Christmas hummingbird [large type] - Bunn, T. Davis, 1952- (Bunn, T. Davis, 1952- Miramar Bay, 2022)
"Ryan Eames is a policewoman and single mother dedicated most of all to her lonely, uniquely gifted son. Stretched thin by double shifts and grappling with an out-of-season coastal wildfire, Christmas cheer feels as far away as a distant carol on a winter night. Until duty draws her into the life of a stranger. Ethan Lange is alive because Ryan reached his canyon home before the blaze. Christmas is only days away, and Ethan has lost everything. A man reckoning with a painful past, it's not the first time he's been forced to start over. At least now it's in the redeeming embrace of Miramar Bay. Forging an animal rescue operation, Ryan and Ethan first unite by their cause and the rally of a close-knit community. But it's Ryan's extraordinary child who draws them into something deeper and surprising. Something to be thankful for. Now with every beat of their hearts, Christmas in Miramar Bay looks to be a season of love, healing, and sweet mercies that will be remembered for a lifetime."--